3‑Alkynylindoles as Building Blocks for the Synthesis of Electronically Tunable Indole-Based Push–Pull Chromophores - Erden, Kübra; Dengiz, Cagatay (Journal of organic chemistry, 2022)
In this study, two different classes of push–pull chromophores were synthesized in modest to excellent yields by formal [2+2] cycloaddition-retroelectrocyclization (CA-RE) reactions. N-Methyl indole was introduced as a new donor group to activate alkynes in the CA-RE transformations. Depending on the side groups’ size and donor/acceptor characteristics, N-methyl indole-containing compounds exhibited λmax values ranging between 378 and 658 nm. The optoelectronic properties of the reported D–A-type structures were studied by UV/vis spectroscopy and computational studies. The complete regioselectivity observed in the products was elaborated by one-dimensional (1D) and two-dimensional (2D) NMR studies, and the electron donor strength order of N-alkyl indole and triazene donor groups was also established. The intramolecular charge-transfer characteristics of the target push–pull chromophores were investigated by frontier orbital depictions, electrostatic potential maps, and time-dependent density functional theory calculations. Overall, the computational and experimental results match each other. Integrating a new donor group, N-alkyl indole, into the substrates used in formal [2+2] cycloaddition-retroelectrocyclizations has significant potential to overcome the limited donor-substituted substrate scope problem of CA-RE reactions.